Pengembangan Bahan Ajar Berbasis Genially terhadap Materi Menulis Teks Berita Siswa Kelas VII UPTD SMP Negeri 5 Gunungsitoli - Fentri Zebua; Lestari Waruwu; Noibe Halawa; Mastawati Ndruru (Pusat riset dan Inovasi Nasional, 2025)
This study aims to develop Genially-based teaching materials for the topic of news text writing for Grade VII students at UPTD SMP Negeri 5 Gunungsitoli. The research method used is Research and Development (R&D) with the Borg and Gall model, which consists of ten stages ranging from identifying potentials and problems to mass production. The research subjects were students from class VII-E (6 students: 3 male and 3 female) and class VII-D (31 students: 15 male and 16 female). The validation results of the teaching materials indicated a very high level of feasibility, with scores from three experts: material expert (100%), language expert (100%), and design expert (96.6%). A practicality test conducted on a small group yielded a score of 96.11%, categorized as